Bundled green services drive farmer adoption of climate-smart agriculture - Afari-Kwarteng, Jemima; Adedeji, Oluwaseun (Technical Centre for Agricultural and Rural Cooperation, 2019)
Experience with climate-smart agriculture (CSA) initiatives increasingly shows that delivering green services in isolation is an ineffective approach that produces disappointing outcomes. The provision of ‘bundled' products which are suited to farmers' re